Reliability index of distributed parameter system - Pho, Nguyen Van (Vietnam Journal of Mechanics, 2000)
In this paper, a method to determine the reliability index of distributed parameter systems by using a method of approximation the multi-condition dependent probability by a one-condition dependent probability is proposed. Therefore, the problem of the reliability index of distributed parameter system is transformed into the defined case. To illustrate for the method, the reliability index of air tube is considered.